Kajian Kriminologis terhadap Kekerasan yang Dilakukan oleh Pasangan Kumpul Kebo: Studi Kasus di Wilayah Hukum Polres Manggarai Barat - Yeremias Bagul; Heryanto Amalo; Rosalind Angel Fanggi (Universitas Sains dan Teknologi Komputer, 2024)
Violence in cohabiting couples is a problem currently occurring in East Nusa Tenggara Province, West Mangarai Regency. Based on the results of research on July 3 2023 at the West Manggarai Police, the West Manggarai District Prosecutor's Office and the West Manggarai District Court found that there were 4 perpetrators in cases of violence in cohabiting couples. The main problem in this research is the factors that cause violence in cohabiting couples and efforts to overcome violence committed by cohabiting couples. This research is empirical legal research that examines all legal events that occur through a case approach. Data collection was carried out in two ways, namely interviews and document study. The data that has been obtained will then be presented in a qualitative descriptive manner. The research results show that (1) The factors that cause violence perpetrated by cohabiting couples are psychological, economic, environmental, the role of the victim and cultural factors. (2) Countermeasures carried out by the West Manggarai Police, the West Manggarai District Prosecutor's Office and the West Manggarai District Court. Therefore, suggestions for the results of this research are (1) It is recommended that men be able to treat their female partners as well as possible, (2) The parties are expected to understand each other's position as unmarried couples so that they are able to carry out their respective obligations. well. (3) For law enforcers and all parties who are obliged to be more enthusiastic in socializing cases of violence in the social environment in the West Manggarai jurisdiction.